The Role of Daily Islamic-Based Activities in Shaping Discipline of Early Childhood at RA Maunaturrahman NW Mekar Kute in the 2025/2026 Academic Year - Ahmad Gozali; Sauriati Aprilia (Journal of Islamic Religious Studies, 2025)
This study aims to examine the role of daily Islamic-based activities in shaping the discipline of early childhood at RA Maunaturrahman NW Mekar Kute in the 2025/2026 academic year. This research employed a qualitative approach with a descriptive design, allowing the researcher to understand the real experiences of children, teachers, and the school principal regarding the habituation of Islamic activities in the early childhood education environment. The informants consisted of the head of RA, three teachers, and 50 students, selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that daily Islamic-based activities, such as greetings, joint prayers, congregational dhuha prayers, short tadarus sessions, and queue habituation, were implemented in a structured and consistent manner, thereby shaping children’s disciplined behavior. The children became accustomed to being punctual, taking turns, respecting their peers, and following rules orderly. The role of teachers and the school principal as role models, along with parental support, were the main factors supporting the success of this habituation. The challenges encountered included children’s natural tendency to play and the limitations of worship facilities, such as prayer garments, prayer mats, and children’s Qur’ans. Overall, this study confirms that daily Islamic-based activities are effective as a means of fostering discipline in early childhood, both at school and at home.